1971
DOI: 10.1111/j.1365-2133.1971.tb07195.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Acne Vulgaris in Adolescence

Abstract: SUMMARY.— We examined 1555 school children aged 8 to 18 and graded them according to the presence and severity of acne lesions on the face and neck. Comedones were present in a large proportion of even the youngest children and were virtually universal by the mid‐teens. Clinical acne appeared 2 years earlier in girls than boys and the maximum prevalence was reached at age 14 in girls and 16 in boys. Thereafter the prevalence of the more severe grades of acne continued to increase steadily in boys, but declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
127
2
8

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(156 citation statements)
references
References 4 publications
19
127
2
8
Order By: Relevance
“…The acne severity was assessed with the acne grading criteria defined by Burton et al [3] (Table 1). …”
Section: Clinical Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The acne severity was assessed with the acne grading criteria defined by Burton et al [3] (Table 1). …”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Acne is one of the most common skin conditions and accounts for more than 30% of all visits to dermatologists [1][2][3]. Topical and systemic antibiotics, retinoids, and chemical peelings have been used conventionally for acne treatment with variable success rates [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, maximum number of patients belonged to the age group 16-20 years with 61 (51%), followed by 11-15 years with 25 (21%) patients. Burton et al [3] reported the peak age of acne as between 14-17 years in females and 16-19 years in males. Adityan et al [4] reported most common age group involved was 16 to 20 years (59.8%).…”
Section: Resultsmentioning
confidence: 99%
“…1 Teenagers and young adults are usually affected, though 10 -20 % of the adult population may experience some form of the skin disorder. 2 Multiple factors including excess sebum production, follicular hyper keratinization, colonization of bacteria like Propionibacterium acnes (P. acnes), and resultant inflammation are responsible for the pathogenesis of acne.…”
Section: Introductionmentioning
confidence: 99%